The interrelationship between human resource management and corporate strategy - R. Abratt (South African Journal of Business Management, 1983)
The involvement of personnel executives in the strategic planning of the enterprise is a controversial issue. Personnel has been considered a staff function which deals with day-to-day administration issues and as such has often been regarded with some contempt by the top management team. Concomitantly many firms are viewing the personnel function in an entirely different light; it now participates in the decision making of the company. The objectives of this paper are two fold: firstly to find a link between corporate strategy and human resource management and secondly, to find out whether personnel managers of quoted South African companies participate in corporate strategy formation. The company comprises of a number of varying dimensions and systems. Every organizational dimension and system must be consistent, not only with the strategy, but also with every other organizational dimension and system. The personnel department is often excluded from the corporate planning process. This exclusion represents a high cost to the total system due to less than optimum usage of an organization's human resources. This paper discusses the need for planning by management with particular reference to manpower planning in relation to corporate planning.